2019
DOI: 10.31025/2611-4135/2019.13877
|View full text |Cite
|
Sign up to set email alerts
|

Case Study on Enhanced Landfill Mining at Mont-Saint-Guibert Landfill in Belgium: Characterization and Potential of Fine Fractions

Abstract: Within the framework of the "EU Training Network for Resource Recovery through Enhanced Landfill Mining -NEW-MINE", around 374 Mg of waste were excavated from a landfill site in Mont-Saint-Guibert, Belgium. Parameters such as bulk density, water content, particle size distribution and material composition of the fine fractions (material <90 mm) were determined and analyzed. The present investigation has the main objective to document and disseminate the findings on the material characterization of the fine fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Mechanical processing of the fine fractions 90 to 4.5 mm yielded median amounts of approx. 37.2 wt.% inert, 9.0 wt.% combustibles and 1.7 wt.% total metals in dry state of the total amount of fine fractions <90 mm (Hernández Parrodi et al, 2019c). In the latter case study, the extension of mechanical processing from a particle size of 10 mm to 4.5 mm increased the amount of recovered materials by around 10 wt.% (Hernández Parrodi et al, 2019c), thus representing an additional amount of resource potential in comparison with previous studies in which particle sizes below 10 mm were not processed (Wanka, Münnich, & Fricke, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical processing of the fine fractions 90 to 4.5 mm yielded median amounts of approx. 37.2 wt.% inert, 9.0 wt.% combustibles and 1.7 wt.% total metals in dry state of the total amount of fine fractions <90 mm (Hernández Parrodi et al, 2019c). In the latter case study, the extension of mechanical processing from a particle size of 10 mm to 4.5 mm increased the amount of recovered materials by around 10 wt.% (Hernández Parrodi et al, 2019c), thus representing an additional amount of resource potential in comparison with previous studies in which particle sizes below 10 mm were not processed (Wanka, Münnich, & Fricke, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…37.2 wt.% inert, 9.0 wt.% combustibles and 1.7 wt.% total metals in dry state of the total amount of fine fractions <90 mm (Hernández Parrodi et al, 2019c). In the latter case study, the extension of mechanical processing from a particle size of 10 mm to 4.5 mm increased the amount of recovered materials by around 10 wt.% (Hernández Parrodi et al, 2019c), thus representing an additional amount of resource potential in comparison with previous studies in which particle sizes below 10 mm were not processed (Wanka, Münnich, & Fricke, 2017). However, fine fractions <4.5 mm which, due to their fine grain size are not suitable for separation either manually or using sensor-based technologies, remain highly challenging (Küppers, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…44 ha, which has been in operation since 1937 as a sand quarry and was transformed in 1958 into a disposal site for MSW, C&D waste and non-hazardous industrial waste (ISSeP, 2011). The excavation took place in the oldest part (red delimited area in Figure 1a) which covers a surface of 14 ha, storing circa 5.7 million m 3 of waste (Hernández Parrodi et al, 2019;IGRETEC, 1994).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Nevertheless, taking into account that relevant amounts of grouped material fractions other than "Agglomerated fines <10 mm" (i.e. "Combustibles", "Inert", "Fe metals", "Non-Fe metals" and "Others") were not identified below a particle size of 3.15 mm during the material characterization of the fine fractions (Hernández Parrodi et al, 2019a), the sorting of the fine fractions into "Combustibles + Others", "Inert", "Fe metals" and "Non-Fe metals" would only make sense above 3 mm. Thus, given that the curve for 10 wt.% water content could be expected to be very close to the one in dry state, it was concluded that a reduction of the original water content (median of 27 wt.%) to around 15 wt.% would suffice to allow an adequate mechanical processing of the fine fractions above 3 mm.…”
Section: Optimal Water Contentmentioning
confidence: 99%
“…These grouped ma- terial fractions are also in agreement with those of the material characterization presented in Table 1, except for the fraction "Fine fractions <4.5 mm (Soil-like material)", which has a particle size <4.5 mm and, hence, corresponds partially to fraction "Fine fractions <10 mm (Mixed materials)" and fraction "Others" of the material characterization, from which most part ended up in the fraction "Combustibles" of the mechanical processing due to its characteristics. Unlike material characterization, which was performed by hand down to a particle size of 10 mm, the mechanical processing was implemented down to 4.5 mm, since small amounts of recoverable materials were still visually identified below 10 mm and above 3.15 mm in the material characterization (Hernández Parrodi et al, 2019a). Thus, most of the fraction "Fine fractions <10 mm (Mixed materials)" is composed of the "Fine fractions <4.5 mm (Soil-like material)" fraction, whereas the remainder is expected to be distributed among the rest of the grouped material fractions (i.e.…”
Section: Mass Balance Of Grouped Materials Fractions Per Particle Sizementioning
confidence: 99%